Sosialisasi Pengenalan dan Penggunaan Aplikasi CANVA dalam Membuat Media Pembelajaran yang Menarik Bagi Guru Sekolah Dasar - Indra Perdana; Yoan Theasy; Syarah Veniaty; Rahmat Winata; Muhammad Rizaldi; Fajar; Kristanoval (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2024)
The socialization of the introduction and use of the Canva application aims to improve the ability of elementary school teachers to create interesting and interactive learning media. Interesting learning media can increase student motivation and the effectiveness of the teaching and learning process. This community service activity was carried out at Elementary School 1 Pahandut Palangka Raya involving 25 teachers as participants. Through the workshop method, participants were given an understanding of Canva's features and how to use them to design learning media. This activity has several stages, including: Presentation: Introduction to the Canva application, available features, and its benefits in education, Demonstration: Showing the steps for using Canva to create learning media, Practice: Teachers are invited to create their own learning media with guidance from the facilitator, and Discussion: Question and answer session to explore the use of Canva. The results of the activity showed an increase in teacher skills in using the application, as well as high enthusiasm for applying technology in the teaching and learning process. It is hoped that with the implementation of this application, the learning process can be more interesting and effective, and increase student motivation in learning. This activity also opens up opportunities for follow-up in the form of further mentoring and training.    Abstrak Sosialisasi Pengenalan dan Penggunaan Aplikasi Canva bertujuan untuk meningkatkan kemampuan guru sekolah dasar dalam menciptakan media pembelajaran yang menarik dan interaktif. Media pembelajaran yang menarik dapat meningkatkan motivasi siswa dan efektivitas proses belajar mengajar. Kegiatan pengabdian masyarakat ini dilaksanakan di Sekolah Dasar Negeri 1 Pahandut Palangka Raya dengan melibatkan 25 guru sebagai peserta. Melalui metode workshop, peserta diberikan pemahaman tentang fitur-fitur Canva dan cara memanfaatkannya untuk desain media pembelajaran. Kegiatan ini memiliki beberapa tahap antara lain:  Presentasi: Pengenalan aplikasi Canva, fitur-fitur yang tersedia, dan manfaatnya dalam pendidikan, Demonstrasi: Menunjukkan langkah-langkah penggunaan Canva untuk membuat media pembelajaran, Praktik: Guru diajak untuk membuat media pembelajaran sendiri dengan bimbingan dari fasilitator, dan Diskusi: Sesi tanya jawab untuk mendalami penggunaan Canva. Hasil dari kegiatan menunjukkan peningkatan keterampilan guru dalam menggunakan aplikasi, serta antusiasme yang tinggi untuk menerapkan teknologi dalam proses belajar mengajar. Diharapkan, dengan penerapan aplikasi ini, proses pembelajaran dapat menjadi lebih menarik dan efektif, serta meningkatkan motivasi siswa dalam belajar. Kegiatan ini juga membuka peluang untuk tindak lanjut dalam bentuk pendampingan dan pelatihan lebih lanjut.